DNA Barcoding of Fish in Mischief Reef—Fish Diversity of a Reef Fish Community From Nansha Islands - Shan, Binbin; Liu, Yan; Yang, Changping; Zhao, Yu; Zhang, Gongjun; Wu, Qiaer; Sun, Dianrong (Frontiers in Marine Science, 2021)
Development of effective conservation and management strategies requires assessments of ecosystem biodiversity status, especially in understudied hotspots of global fish diversity. Coral reefs are important habitats for fishes, with biodiversity hotspots known globally. We present the first data on molecular diversity of fishes of Mischief Reef, the largest atoll in the Nansha Islands. Partial sequences (650 bp) of mitochondrial COI gene (Cytochrome c oxidase subunit I) are used to barcode 209 individuals, representing 101 species, referable to 62 genera, 27 families, 8 orders, and one class. The most abundant orders are the Perciformes (176 specimens, 84.21%), Tetraodontiformes (13 specimens, 6.22%) and Beryciformes (13 specimens, 6.22%). Mean Kimura 2-Parameter genetic distances within genera, families and orders are 4.51%, 13.90%, and 17.63%, respectively. We record Monotaxis heterodon from this region for the first time—a species which may previously have been misidentified as M. grandoculis. In addition, we recognized possible cryptic species of Lethrinus olivaceus based on significantly diverging barcode sequences. Barcode data provide new insights into fish diversity of Mischief Reef, important for developing further research on this fauna, and for its conservation.